The Association of Genetic and Dietary Exposures with Gestational Diabetes Mellitus Risk - Ha, Vanessa (My University, 2019)
Background: Although lifestyle modification is the cornerstone of GDM management, the evidence base on which dietary recommendations to prevent GDM is diverse and has not been synthesized in a consistent fashion. Objectives: The overall objective of this thesis is to assess the relationship of diet patterns, foods, and nutrients with GDM risk. Specifically, we seek to: 1) Quantify the relationship between dietary factors and GDM and metabolic disorders of pregnancy; 2) Compare the effects of dietary factors on markers of glycemic control, such as fasting glucose, fasting insulin, HbA1c, and the homeostatic model assessment for insulin resistance (HOMA-IR); 3) Assess the association and interaction between carbohydrate quality, and genetic load on the risk of developing GDM using data from 2 prospective birth cohort studies. Methods: We follow the approach set by the Cochrane Group’s Handbook for Systematic Review of Interventions to conduct meta-analyses and assess the quality of the evidence using the GRADE (Grading of Recommendations, Assessment, Development and Evaluation) approach. We analyze prospective cohort data of 2,504 women from the CHILD and START studies, which enrolled women of White-Caucasian and South Asian ethnicity. We quantify carbohydrate quality by deriving the glycemic index and load (GL), and total and added sugar intake. We construct a gene score using 102 loci that were previously associated with type 2 diabetes in genome-wide association studies. Results: 1) The meta-analysis identified high-quality evidence that red meat increases GDM risk; however, most associations of foods and nutrients with GDM and other metabolic disorders of pregnancy are of low-quality; 2) The network meta-analysis identified that most dietary interventions given with gestational weight gain advice will lower fasting glucose; 3) In South Asians, a high GL coupled with a high genetic load increased GDM risk six fold, but a high total sugar intake in the presence of a high genetic load reduced GDM risk. This paradoxical finding may be explained by a high correlation between total sugars and other healthy foods. Conclusions: Few valid associations between dietary factors and GDM risk exist. GL and total sugars may modify the genetic risk of GDM in South Asians but not in White-Caucasians. Further research is needed to determine effective interventions that can assist women in adopting healthier eating habits during pregnancy.
Keywords: Gestational Diabetes Mellitus; Diet; Genetics; Diet x Gene Interaction; Pregnancy; South Asian; Pregnancy Complications; Hypertensive Disorder of Pregnancy; Gestational Weight Gain; Prospective Cohort; Systematic Review; Meta-Analysis; Maternal Health